Analisis pola kelekatan guru terhadap motivasi belajar siswa fase B studi kasus di kelas 3 dan 4 SDN 2 Kramatmulya tahun ajaran 2024/2025 - Ningsih, Sindi Pitria; Lestari, Myrna Apriany; Oktaviani, Ndaru Mukti (COLLASE (Creative of Learning Students Elementary Education), 2025)
Abstract This research is based on the importance of the emotional relationship between teachers and students in supporting learning motivation. Positive attachment is believed to be able to form a sense of security, increase participation, and encourage student achievement in the elementary school environment. This study aims to analyze the pattern of teachers' attachment to the learning motivation of phase B students (grades 3 and 4) at SDN 2 Kramatmulya. The method used is a qualitative approach with observation, interview, questionnaire, and documentation study techniques. The results of the study show that the secure attachment pattern dominates, with the characteristics of a supportive and responsive teacher-student relationship, so that it has a very positive effect on learning motivation. The avoidant attachment pattern was found in small numbers and negatively impacted student enthusiasm. Meanwhile, the pattern of anxious attachment appears non-dominantly, causing students' motivation to learn to be unstable. A pattern of disorganized attachment was not found in this study. This research corroborates Bowlby's theory of attachment that a secure relationship between teacher and student is an important foundation in the development of children's learning motivation. Keywords: Attachment Pattern, Learning Motivation, Phase B, SDN 2 Kramatmulya Abstrak Penelitian ini didasari oleh pentingnya hubungan emosional antara guru dan siswa dalam menunjang motivasi belajar. Kelekatan yang positif diyakini mampu membentuk rasa aman, meningkatkan partisipasi, dan mendorong prestasi siswa di lingkungan sekolah dasar. Penelitian ini bertujuan untuk menganalisis pola kelekatan guru terhadap motivasi belajar siswa fase B (kelas 3 dan 4) di SDN 2 Kramatmulya. Metode yang digunakan adalah pendekatan kualitatif dengan teknik observasi, wawancara, angket, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa pola secure attachment mendominasi, dengan karakteristik hubungan guru-siswa yang suportif dan responsif, sehingga berpengaruh sangat positif terhadap motivasi belajar. Pola avoidant attachment ditemukan dalam jumlah kecil dan berdampak negatif terhadap antusiasme siswa. Sementara itu, pola anxious attachment muncul secara tidak dominan, menyebabkan motivasi belajar siswa cenderung tidak stabil. Pola disorganized attachment tidak ditemukan dalam penelitian ini. Penelitian ini menguatkan teori kelekatan Bowlby bahwa hubungan aman antara guru dan siswa menjadi fondasi penting dalam perkembangan motivasi belajar anak. Kata kunci: Pola Kelekatan, Motivasi Belajar, Fase B, SDN 2 Kramatmulya